Manajemen Kualitas Produk UMKM Sebagai Strategi Ketahanan dan Keberlanjutan Bisnis: Studi Evaluasi Kandungan Kimia Produk Olahan Peternakan - Damayanti, Rossa; Fenita, Yosi; Santoso, Urip; Hambali, Imam; Hardinata, Dodi; Fitri, Linda; Rahman, Arif (Seminar Nasional Manajemen, 2025)
Food-based MSMEs, particularly those engaged in livestock product processing, play an important role in the local economy and in meeting community nutrition needs. However, inconsistent product quality remains a major challenge in improving competitiveness. This study evaluates the quality of MSME products using proximate analysis (moisture, ash, protein, fat, fiber) on several processed products. The results show variations in quality among producers. The average protein content of meatballs (7.2%) did not meet the minimum Indonesian National Standard (8.0%), while nuggets nearly met the requirement (11.9% vs. 12.0%). These findings indicate weak standardization of formulation and quality control. From a management perspective, product quality is the key to business resilience and sustainability, especially in the post-digital era. Amid increasingly intense competition in digital marketplaces, consistency of product quality determines whether MSMEs can survive or not. This study emphasizes that evidence-based quality management, product innovation, and collaborative governance are fundamental prerequisites for building resilient, sustainable, and adaptive MSMEs in the post-digital era.